Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT. Kereta Api Indonesia Divre II Sumbar - Gulo, Junianus; Salfadri, Salfadri; Delvianti, Delvianti (Fakultas Ekonomi, Universitas Ekasaktii, 2023)
The research aims include: (1) To identify the influence of organizational culture on employee performance at PT. Indonesian Railways (Persero) Division II West Sumatra. (2) To identify the influence of the work environment on employee performance at PT. Indonesian Railways (Persero) Division II West Sumatra. (3) To identify the influence of organizational culture and work environment together on employee performance at PT. Indonesian Railways (Persero) Division II West Sumatra. The method for collecting data is field study and literature study. Data uses primary and secondary sources. For the research population, all employees at the PT office were used. Kereta Api Indonesia (Persero) West Sumatra Division II with a total of 510 employees and the sample in this study was 83 people. The analysis method uses multiple linear regression analysis. The results of the analysis found that (1) Organizational culture significantly influences employee performance at PT. KAI (Persero) West Sumatra Division II. (2) The work environment significantly influences employee performance at PT. KAI (Persero) West Sumatra Division II. (3) Simultaneously, organizational culture and work environment significantly influence employee performance at PT. KAI (Persero) West Sumatra Division II.